2018
DOI: 10.1016/j.dental.2018.06.010
|View full text |Cite
|
Sign up to set email alerts
|

Impact of crystallization firing process on the microstructure and flexural strength of zirconia-reinforced lithium silicate glass-ceramics

Abstract: The CFP had a direct influence on the flexural strength and microstructural characteristics of both ZLS materials.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
57
0
3

Year Published

2019
2019
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 69 publications
(64 citation statements)
references
References 17 publications
(30 reference statements)
4
57
0
3
Order By: Relevance
“…Moreover, the relatively smooth zone of slow crack propagation suggests that the crack may have propagated in the glassy matrix instead of being impeded by the presence of crystals. This could explain the relatively low flexural strength and fracture toughness values for Obsidian, perhaps the result of an incomplete crystallization process …”
Section: Discussionmentioning
confidence: 99%
“…Moreover, the relatively smooth zone of slow crack propagation suggests that the crack may have propagated in the glassy matrix instead of being impeded by the presence of crystals. This could explain the relatively low flexural strength and fracture toughness values for Obsidian, perhaps the result of an incomplete crystallization process …”
Section: Discussionmentioning
confidence: 99%
“…Fully crystallized ZLS glass-ceramics can be cemented after milling and glazing or polishing, whereas pre-crystallized ZLS glass-ceramics require a further crystallization firing process combined with glazing, additional glazing, or polishing to reach its final esthetic and physical properties. 34 Studies reported in the literature investigated the surface characteristics and optical properties (glazing or polishing) of ZLS glassceramics. 6,11 However, data on the glazing efficiency with or without crystallization are limited.…”
Section: Discussionmentioning
confidence: 99%
“…3 Bahgat et al 38 reported that the higher translucency of ZLS glass-ceramic might be due to its lower (0.5 μm) and more homogeneous crystalline structures (2 types). Riquieri et al 34 also reported many differences in the microstructure of ZLS glassceramics before and after crystallization firing; zirconia grains decreased and nanocrystalline lithium metasilicate peaks (Li2SiO3) were more intense in X-ray diffraction after the crystallization firing process (CFP). Although microstructural differences in the ZLS glassceramic were not evaluated in the present study, the difference in TP values may be due to microstructural changes in the ZLS glass-ceramic and the glazing materials during firing.…”
Section: Discussionmentioning
confidence: 99%
“…Incorporation of ZrO 2 particles into the glass matrix is an effective method to improve the mechanical properties of glass-ceramics [60,68,71]. The strengthening mechanism of ZrO 2 reinforced glass-ceramics is schematically demonstrated in Figure 11a.…”
Section: Zro 2 -Reinforced Glass-ceramicsmentioning
confidence: 99%